Health behaviors and education in Turkey - Aysıt Tansel; Deniz Karaoglan (Turkish Economic Association, 2014)
This is the first study which provides empirical analysis of the variation in health behaviors for adult men and women in Turkey which is a developing country. The health behaviors considered are smoking, drinking, fruit and vegetable consumption, exercise and body mass index (BMI). We find that in Turkey education is the most important factor that affects the health behaviors. The results indicate that smoking is positively associated with education at all levels with a decreasing effect with the level of education unlike in the developed countries. This result indicates that smoking is a serious public health problem in Turkey at all levels of education. Further, alcohol consumption and schooling are positively related and it increases by the level of education. Higher educated individuals clearly eat more fruits, vegetables and exercise more and their BMI levels are in the normal range compared to less educated and illiterate. We also highlight the importance of demographic factors, labor market status and household income. We use Health Survey of Turkish Statistical Institute (TURKSTAT) for years 2008, 2010 and 2012. This study will provide a baseline for further studies on the various aspects of health behaviors in Turkey.
Keywords: I10; I12; I19; 330; Health Behaviors; Education; Demographic Factors; Turkey